Decision Making in Organizations: Intuition, Information, and Religiosity - B. George (Ekonomika Nauki)
Previous research in experimental psychology suggests that religious belief is influenced by one’s general tendency to rely on intuition rather than information. A corollary emerging from this based on balance theory is that managers who are religious might make more intuition-based decisions than their counterparts who are not religious. The latter group might tend to make more information-based decisions. Recent research also indicates that the use of scientific method, a close cousin of information-based decision making, triggers moral behavior. Employing critical incident technique, the present researchers test this potential relationship among business executives at various ranks, various cultural contexts, and holding various religious beliefs. Our analysis indicates that theist managers, both gnostic and agnostic, preferred intuitive decision making. Likewise, both gnostic and agnostic atheist managers preferred information-based decision making. Also, atheist managers articulated better logical explanations as to why their decisions were morally correct.